40.6k views
3 votes
Simplify. 6√20−3√8
Enter your answer, in simplest radical form

2 Answers

4 votes

Answer:

Explanation:

√8= √4√2 = 2√2

√20 = √4√5 = 2 √5

6√20−3√8 = 12√5 - 6√2

User Mghicks
by
5.9k points
7 votes

♫ - - - - - - - - - - - - - - - ~Hello There!~ - - - - - - - - - - - - - - - ♫


√(20) can be simplified to 2
√(5)

Multiply 2 by 6 to get the simplified version for part 1

=
12√(5)


√(8) can be simplified to
2√(2)

Multiply 2 by 3 to get the simplified version:

=
6√(2)

It would be:


12√(5) - 3√(8)

➶ Hope This Helps You!

➶ Good Luck (:

➶ Have A Great Day ^-^

ʜᴀɴɴᴀʜ ♡

User Shoham
by
6.3k points